2022
DOI: 10.1021/acscatal.1c04580
|View full text |Cite
|
Sign up to set email alerts
|

Au(I)/Au(III) Catalytic Allylation Involving π-Allyl Au(III) Complexes

Abstract: A (MeDalphos)AuCl complex was found to efficiently catalyze the cross-coupling of indoles and allyl acetates/alcohols. The reaction tolerates many functional groups and selectively affords the branched C3-allylated products from both αand γ-substituted allyl substrates. It takes the advantage of the hemilabile character of the P ∧ N ligand. The C(sp 2 )−C(sp 3 ) coupling operates via a Au(I)/ Au(III) redox cycle and involves a dicationic π-allyl Au(III) complex as a key intermediate. In this case, the allyl mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 65 publications
(83 reference statements)
2
31
0
Order By: Relevance
“… 41 For instance, in 2019 Bourissou and coworkers reported the regioselective Au( i )/Au( iii )-catalyzed C3 arylation of indoles, which is rarely attained by other transition metals ( Scheme 1a ), 49 additionally they described the Au( i )/Au( iii ) catalyzed C3 allylation of indoles using allyl alcohols or allyl acetates. 50 Significantly, two independent reports by the groups of Patil 51 and Bourissou 52 disclosed the C sp 2 –N cross-coupling reactions of aryl iodides with amines mediated by the MeDalphos-enabled Au( i )/Au( iii ) catalysis ( Scheme 1a ). In 2020, Bourissou and Patil groups independently showed that the oxidative addition of aryl iodides and π-activation of olefins can be merged by the Au( i )/Au( iii ) platform using (MeDalphos)AuCl as catalyst, which involves the oxy- and aminoarylation reactions of alkenols and alkenamines ( Scheme 1a ).…”
Section: Introductionmentioning
confidence: 99%
“… 41 For instance, in 2019 Bourissou and coworkers reported the regioselective Au( i )/Au( iii )-catalyzed C3 arylation of indoles, which is rarely attained by other transition metals ( Scheme 1a ), 49 additionally they described the Au( i )/Au( iii ) catalyzed C3 allylation of indoles using allyl alcohols or allyl acetates. 50 Significantly, two independent reports by the groups of Patil 51 and Bourissou 52 disclosed the C sp 2 –N cross-coupling reactions of aryl iodides with amines mediated by the MeDalphos-enabled Au( i )/Au( iii ) catalysis ( Scheme 1a ). In 2020, Bourissou and Patil groups independently showed that the oxidative addition of aryl iodides and π-activation of olefins can be merged by the Au( i )/Au( iii ) platform using (MeDalphos)AuCl as catalyst, which involves the oxy- and aminoarylation reactions of alkenols and alkenamines ( Scheme 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…7B. 19 In this transformation, the activation of 7d with AgSbF 6 to a cationic intermediate facilitated C–C bond formation in the subsequent intramolecular reductive elimination process. Cationic Au complexes undergo reductive elimination at exceptionally fast rates in comparison to neutral Au( iii ) complexes.…”
Section: Elementary Stepsmentioning
confidence: 99%
“…Gold catalysis has been widely developed in the past several decades, and gold complexes have emerged as a powerful catalyst for the functionalization of C–C multiple bonds of alkenes and alkynes. , However, due to the high redox potential of the Au I /Au III couple ( E 0 = +1.41 V), the Au I /Au III catalytic cycle is full of difficulties. Thus, the use of a strong, sacrificial two-electron oxidant becomes necessary to enable the access of the Au I /Au III catalytic cycle and to achieve the desired cross-coupling transformations. For a long time, remarkable effort was dedicated to promote the catalytic redox process of the Au I /Au III couple with the use of an external oxidant to expand the scope of the gold catalysis. In recent years, other strategies like strain release, , ligand design, , and photoredox catalysis have been greatly developed to promote oxidant-free Au I /Au III catalysis. By using these strategies, Hashmi et al, Bourissou et al, Patil et al, Hammond et al, and Shi et al have made great progress in the cross-coupling reactions of carbon–carbon or carbon–heteroatom bonds.…”
Section: Introductionmentioning
confidence: 99%